2014
DOI: 10.1016/j.lingua.2014.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Order in NP conjuncts in spoken English and Japanese

Abstract: In the emerging field of cross-linguistic studies on language production, one particularly interesting line of inquiry is possible differences between English and Japanese in ordering words and phrases. Previous research gives rise to the idea that there is a difference in accessing meaning versus form during linearization between these two languages. This assumption is based on observations of language-specific effects of the length factor on the order of phrases (short-before-long in English, long-before-sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 44 publications
2
13
0
Order By: Relevance
“…Nevertheless, it only exerts a mild effect in Chinese. This relates to previous studies, which have shown that whether the preference for DLM exists and its efficacy are dependent on the headedness of the specific structures for languages with different typological characteristics (Lohmann and Takada, 2014;. The argument status of the PP also has a pronounced effect on the orderings.…”
Section: Discussionsupporting
confidence: 81%
“…Nevertheless, it only exerts a mild effect in Chinese. This relates to previous studies, which have shown that whether the preference for DLM exists and its efficacy are dependent on the headedness of the specific structures for languages with different typological characteristics (Lohmann and Takada, 2014;. The argument status of the PP also has a pronounced effect on the orderings.…”
Section: Discussionsupporting
confidence: 81%
“…Experiment 1 tested the role of sortal information structure, and found that which wh-word functioned as the sortal key had a significant effect on participants' choice of position for the wh-words: sortal keys were preferred fronted. This was in the direction of Kuno's (1982) hypothesis, but the effect did not show up uniformly across wh-words, and in fact appeared as the inverse in some cases. Experiment 2 tested the hypotheses of Dayal (1996) and Willis (2008) that fronted whphrases need to have a smaller domain than their in-situ counterparts, because they are required to be exhausted over (perhaps due to being interpreted as universal quantifiers).…”
Section: Resultsmentioning
confidence: 74%
“…EXPERIMENT 1: SORTAL KEYS. The first experiment evaluates the role that discourse context plays in determining which wh-phrase is used as the 'sortal key', in the sense of Kuno (1982), and whether there is a preference for using the higher or lower wh-phrase as said key. It is a further development of an experiment piloted by Constant (2014) to test these intuitions: 'subjects... were asked to pick the best title for a list of frequently asked questions on a college admissions website.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the major factors determining serial order is the short-beforelong principle (e.g. Behaghel 1909, Hawkins 1994, Lohmann & Takada 2014). Hawkins's (1994) performance theory relies, among other things, on the distance between the heads of phrases.…”
Section: On the Role Of Distancementioning
confidence: 99%